Structural Connectivity in Down Syndrome and Alzheimer’s Disease - Saini, Fedal; Dell’Acqua, Flavio; Strydom, Andre (Frontiers in Neuroscience, 2022)
Down Syndrome (DS) arise from the triplication of chromosome 21 which leads to an atypical neurodevelopment and the overproduction of the amyloid precursor protein, predisposing to early Alzheimer’s disease (AD). Not surprisingly, trisomy 21 is widely considered as a model to study predementia stages of AD. After decades in which the neural loss was the main focus, research in AD is now moving toward the understanding of the neurodegenerative aspects affecting white matter. Being motivated by the development of MRI-based diffusion techniques, this shift in focus has led to several exploratory studies in both young and older individuals with DS. In this review, we synthesise the initial efforts made by researchers in characterising in-vivo structural connectivity in DS, together with the AD footprint on top of such pre-existing connectivity related to atypical brain development. The white matter structures found to be affected in DS are the corpus callosum and all the main long association fibres, namely the Inferior fronto-occipital fasciculus, the Inferior and Superior longitudinal fasciculus, the Uncinate fasciculus and the cingulum bundle. Furthermore, the cingulum bundle and the corpus callosum appear to be particularly sensitive to early AD changes in this population. Findings are discussed in terms of their functional significance, alongside methodological considerations and implications for future research.